Prevention of STI/HIV between lesbian and bisexual women: a bibliographic research (2013-2017) - Dal Santo, Amanda (2021)
Prevention in STIs/HIV must consider different aspects that can put certain populations in situation of vulnerability. Based on this understanding, this research carried out a bibliographic research about prevention of STIs/HIV among lesbian and bisexual women. The search platforms used were Scielo and the Virtual Health Library (VHL), covering articles in English, Portuguese and Spanish, published between 2013 and 2017. We presented the results and discussion in the form of lines of analysis. These reveal aspects of the vulnerability of the studied public, such as the perception of sexual orientation, race, stigma, unpreparedness of health professionals and lack of knowledge/imprecise knowledge of women related to barrier methods. We point to the need to create policies that address the theme, considering its complexity and the diversity of experiences from the crossing of different social markers. At the end, we indicate suggestions for new studies to be carried out on this theme.Prevention in STIs/HIV must consider different aspects that can put certain populations in situation of vulnerability. Based on this understanding, this research carried out a bibliographic research about prevention of STIs/HIV among lesbian and bisexual women. The search platforms used were Scielo and the Virtual Health Library (VHL), covering articles in English, Portuguese and Spanish, published between 2013 and 2017. We presented the results and discussion in the form of lines of analysis. These reveal aspects of the vulnerability of the studied public, such as the perception of sexual orientation, race, stigma, unpreparedness of health professionals and lack of knowledge/imprecise knowledge of women related to barrier methods. We point to the need to create policies that address the theme, considering its complexity and the diversity of experiences from the crossing of different social markers. At the end, we indicate suggestions for new studies to be carried out on this theme.